Chile's High Growth Economy : Poverty and Income Distribution, 1987-1998 - World Bank (Washington, DC, 2013)
The present study focuses on four main objectives. First, it presents an update of poverty, and income distribution measures, reported in 1997 by the Bank; second, it looks at deficiencies in social services, and how to improve social services targeted to the poor; third, it considers how trends in income distribution could be modified, if taking into account the transfer effect of social programs; and, fourth, it looks at some special issues that impact on poverty, namely unemployment, and the problems of indigenous peoples. Given the relatively high levels of unemployment, the persistence in educational deficits, and the low coverage of social programs amongst the poor, recommendations suggest, respectively, a focus on relevant, job creation aspects, in line with labor market demands, not merely responsive to the renewed economic growth, to include as well, further labor code, and unemployment insurance system reforms; efforts to consolidate, and intensify the quality, and equity in education, particularly tertiary education to advance Chile's human capital; and, improved targeting of social programs, with attention to regional disparities in the allocation of social spending, particularly as it regards poverty among indigenous communities.